Information system integration: a review of literature and a case analysis - Mohamed, Norshidah
The article aims at providing an explanation on information systems integration. It is an account that is part of an on-going research. In the first part of the article, the researchers present the literature review. The findings show the characteristics of information systems integration. The types, levels and perspectives of information systems integration signify these characteristics. The subsequent part of the article uses a single case research approach of an institution in higher education sector. The purpose is to gain insights into the underlying characteristics and challenges of information systems integration in meeting organizational effectiveness while simultaneously assuring governance.